2012
DOI: 10.1016/j.intmar.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Consumer Perceptions toward Mobile Advertising — A Comparison between Japan and Austria

Abstract: Mobile marketing provides an innovative channel for transmitting advertising messages to customers via mobile devices. The growth of mobile advertising in recent years requires that researchers and practitioners understand consumer perceptions of this form of advertising. The purpose of this paper is to investigate factors influencing the perception of mobile advertising in different cultures. Based on samples from Austria and Japan, we empirically examine relevant m-advertising effects. The results suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
185
1
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(211 citation statements)
references
References 65 publications
10
185
1
15
Order By: Relevance
“…Results reflect the notion that the benefits consumers perceive within advertisements are important determinants of whether they attitude to accept this advertising medium. This finding supports the results of the majority of the studies in the literature that have highlighted the importance of utilitarian and hedonic value on the acceptance of SMS advertising (Bauer et al, 2005;Carroll et al, 2006;Liu et al, 2012;Maneesoonthorn and Fortin, 2006;Merisavo et al, 2007;Nasco and Bruner, 2008). Indeed, by the results of this study, the utilitarian value was found to be the most important driver of consumer attitude to receive SMS advertising, and the second most important factor was hedonic value.…”
Section: Discussionsupporting
confidence: 90%
“…Results reflect the notion that the benefits consumers perceive within advertisements are important determinants of whether they attitude to accept this advertising medium. This finding supports the results of the majority of the studies in the literature that have highlighted the importance of utilitarian and hedonic value on the acceptance of SMS advertising (Bauer et al, 2005;Carroll et al, 2006;Liu et al, 2012;Maneesoonthorn and Fortin, 2006;Merisavo et al, 2007;Nasco and Bruner, 2008). Indeed, by the results of this study, the utilitarian value was found to be the most important driver of consumer attitude to receive SMS advertising, and the second most important factor was hedonic value.…”
Section: Discussionsupporting
confidence: 90%
“…Kim & Han (2014) and Yang et al (2013) stated credibility plays a positive and vital role in predicting advertising value of personalized M-ads for South Korean consumers. Similarly, Liu et al (2012) report credibility predicts the advertising value of SMS ads in both Austrian and Japanese context. Bolstering the above findings, it has been disclosed Chinese consumers welcome more credible ads (Xie et al, 2013), search for credibility of personalized mobile advertising applications (Xu et al, 2008) and seek for credibility in personalized M-ads Xu (2006Xu ( -2007 as well.…”
Section: Credibilitymentioning
confidence: 95%
“…The scales and measures used in this study were adapted or replicated from a variety of related sources (Bamba and Barnes, 2007;Liu et al, 2012;Muk, 2007;Radder et al, 2010;Rettie et al, 2005;Zhang and Mao, 2008). Careful attention has been paid in designing the instrument especially in the wording used and ordering of the questions.…”
Section: Scale Developmentmentioning
confidence: 99%